The first application of ceramic balls in a 7.32 m regrinding ball mill - Junquan Lai; Caibin Wu; Chengfang Yuan; Shuncheng Han; Yufeng Wei; Mingjun Leng; Feng Xie; Yuqing Li (Minerals Engineering, 2026)

Seasonal variations in air-sea interface processes and water column biogeochemical regulation mechanisms of PAHs in the South China Sea - Jingwen Shi; Ye Li; Yina Tanli; Mengyang Liu; Yan Lin; Lin Zhang; Mingjun Feng; Hongwei Ke; Xiangrong Xu; Zi-Feng Zhang; Yi-Fan Li; Xuehong Zheng; et al. (Environmental Research, 2026)

Visual and quantitative insight into formation characteristics and sealing effect of CO2 hydrate cap in porous media with fracture channel - Guojun Zhao; Jia-nan Zheng; Yongchen Song; Zijun Feng; Ranjith Pathegama Gamage; Mingjun Yang (Journal of Cleaner Production, 2026)

Impacts of long-term fertilizer reduction and organic substitution on microbe-mediated multi-nutrient in agricultural ecosystems - Zhenling Li; Jiawei Ying; Xiaokang He; Yangyang Li; Guangchun Shan; Chenghong Feng; Mingjun Ding; Gaoxiang Huang; Jia Liu (Agriculture, Ecosystems & Environment, 2026)

Air quality benefits of state-led industrial transfer: A staggered difference-in-differences analysis in Chinese cities - Langang Feng; Jin Hu; Minmin Huang; Muhammad Irfan; Mingjun Hu (Urban Climate, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Identification and evaluation of odor emissions from a petrochemical production area in China - Yunxia Feng; Jinchan Peng; Yirong Guo; Qingrun Li; Anshan Xiao; Rui Dong; Dewu Ding; Mingjun Li (Atmospheric Pollution Research, 2026)

Biogeochemical processes play a decisive role in determining the fate of marine PAHs: A case validation with field measuring and modelling in the Beibu Gulf, South China Sea - Jingwen Shi; Mengyang Liu; Lingxin Chen; Jiandong Ye; Wupeng Xiao; Jinyan Xie; Fajin Chen; Yi-Fan Li; Xuke Chen; Yan Lin; Lin Zhang; Mingjun Feng; et al. (Journal of Hazardous Materials, 2025)

Agricultural plastic films reshape soil microplastic distribution, nitrogen cycle and ecological risks in facility agriculture - Hao Wang; Gaoxiang Huang; Xiaokang He; Guangchun Shan; Zhenling Li; Mingjun Ding; Chenghong Feng; Caixia Yan (Journal of Hazardous Materials, 2025)

Storm water management model simulations of the non-point source pollution load in the northern Anhui plain - Yun Wan; Mingjun Li; Nan Zhang; Mengwan Lin; Yuxuan Li; Peiqing Huang; Yuqi Feng; Bai Sun; Wei Wei; Shuguang Zhu (Ecohydrology & Hydrobiology, 2025)

Warming impedes aquatic plant recovery via enhanced herbivory from insect outbreaks - Peiyu Zhang; Tao Wang; Shaopeng Wang; Eoin J. O'Gorman; Mingjun Feng; Yulu Wang; Huan Wang; Huan Zhang; Min Zhang; Jun Xu (Ecology, 2025)
Climate warming can destabilize ecological communities by altering species interactions. Population outbreaks, defined as rapid, exponential increases in population size within a given spatiotemporal scale, are naturally occurring phenomena with significant ecosystem‐wide consequences. Such outbreaks are expected to increase in frequency under climate change, yet their ecological consequences under warming remain poorly understood. Here, we conducted a large‐scale pond mesocosm experiment (48 mesocosms, each of 2500 L in volume) to show that warming significantly reduced the growth and impeded the regenerative capacity of aquatic plants following the outbreak of an aquatic moth ( Parapoynx diminutalis ). These effects were driven by warming magnifying herbivory, which substantially diminished the growth and recovery of macrophytes, leading to a turbid state dominated by phytoplankton. Our findings provide strong evidence that global warming can destabilize freshwater ecosystems under population outbreaks, risking the loss of basal resources that provide both food and habitat complexity. The cascading effects on the wider food web could lead to widespread loss of taxonomic and functional diversity, impairing essential ecosystem functions and services.

Multi-omics analysis reveals the mechanism of action of Atractylodin against depression - Shengchuan Bao; Mei Feng; XiZhen Zhang; Mingjun Xie; Jing Teng (Journal of Natural Medicines, 2025)

Selective enrichment of potential pathogens and antibiotic resistance genes derived from farmland residual microplastic films - Gaoxiang Huang; Hao Wang; Zhenling Li; Xiaokang He; Guangchun Shan; Peng Wang; Mingjun Ding; Chenghong Feng (Applied Soil Ecology, 2025)

Weak Fault Feature Extraction for AUV Thrusters with Multi-Input Signals - Dacheng Yu; Feng Yao; Yan Gao; Xing Liu; Mingjun Zhang (Journal of Marine Science and Engineering, 2025)
This paper investigates weak fault feature extraction in AUV thrusters under multi-input signal conditions. Conventional methods often rely on insufficient input signals, leading to a non-monotonic mapping between fault features and fault severity. This, in turn, makes accurate fault severity identification infeasible. To overcome this limitation, this paper increases the number of input signals by utilizing all available measurable signals. To address the problems arising from the expanded signal set, a signal denoising method that combines Feature Mode Decomposition and wavelet denoising is proposed. Furthermore, a signal enhancement technique that integrates energy operators and the Modified Bayes method. Additionally, distinct technical approaches for noise reduction and enhancement are specifically designed for different input signals. Unlike conventional methods that extract features directly from raw input signals, for fault feature extraction and fusion, this study transforms the signals into the time, frequency, and time–frequency domains, extracting diverse fault features across these domains. A sensitivity factor selection method is then employed to identify the sensitive features. These selected features are subsequently fused using Dempster–Shafer evidence theory to construct the final fault feature. Finally, fault severity identification is carried out using the classical grey relational analysis. Pool experiments using the “Beaver II” AUV prototype validate the effectiveness of the proposed method.

LC-MS/MS-based metabolomic of pink Auricularia cornea grown on Lycium barbarum sawdust substrate - Lei Ye; Xuezhen Yang; Zhenzhu Huang; Bo Zhang; Qing Tian; Yu Huang; Wei Tan; Mingjun Feng; Xiaolin Li; Hongbin Xu (Food Chemistry, 2025)

Long-term effects of emission reduction measures on PM2.5 sources and children’s lung function in Jinan, China - Deai Yang; Pengcheng Zuo; Mingjun Li; David Lim; Liangliang Cui; Zhihui Feng (Environmental Geochemistry and Health, 2025)

Adaptive trajectory tracking control for underwater vehicle based on hierarchical compensation - Xing Liu; Tong Wang; Baoji Yin; Feng Yao; Mingjun Zhang (Ocean Engineering, 2025)

A simple and effective algorithm to retrieve total suspended matter from GOCI data in Hangzhou Bay, China - Mingjun He; Shuangyan He; Shiming Lu; Yanzhen Gu; Feng Zhou; Xiaobo Ni; Chengyue Zhu; Peiliang Li (Science of The Total Environment, 2025)

The entropy effect on the structure and microwave dielectric properties of high-entropy Lix(MgZnCoNi)(1-x)/4Al2O4-δ ceramics - Mingjun Xie; Yuanming Lai; Pingwen Xiang; Feng Liu; Linqiao Zhang; Xingyue Liao; Huan Huang; Qian Liu; Chongsheng Wu; Yuanxun Li (Chemical Engineering Journal, 2024)

The efficient uptake of uranium by amine-functionalized β-cyclodextrin supported fly ash composite from polluted water - Congcong Chen; Xuan Liu; Xiaoyu Tian; Jiaqi Feng; Yujia Liu; Mingjun Song; Wenkun Zhu; Yong Zhang (Science of The Total Environment, 2024)

Weak Fault Feature Extraction and Enhancement of Autonomous Underwater Vehicle Thrusters Based on Artificial Rabbits Optimization and Variational Mode Decomposition - Dacheng Yu; Mingjun Zhang; Feng Yao; Jitao Li (Journal of Marine Science and Engineering, 2024)
Variational Mode Decomposition (VMD) has typically been used in weak fault feature extraction in recent years. The problem analyzed in this study is weak fault feature extraction and the enhancement of AUV thrusters based on Artificial Rabbits Optimization (ARO) and VMD. First, we introduce ARO to solve the problem of long-running times when using VMD for weak fault feature extraction. Then, we propose a VMD denoising method based on an improved ARO algorithm to address the issue of deteriorations in the fault feature extraction effect after introducing ARO. In this method, chaotic mapping and Gaussian mutation are used to improve ARO to optimize the parameters of VMD. This leads to a reduced running time and improved fault feature extraction performance. We then perform fault feature enhancement. Due to the unsatisfactory enhancement effect of traditional modified Bayes (MB) methods for weak fault features, we introduce energy operators to transform the fault signals into the energy domain for fault feature enhancement. Finally, we add differential processing to the signal to address the issue of certain fault feature values decreasing after introducing energy operators. In the end, the effectiveness of the proposed methods is verified via pool experiments on a “Beaver II” AUV prototype.

Crocin alleviates neurotoxicity induced by bupivacaine in SH-SY5Y cells with inhibition of PI3K/AKT signaling - Lili Lin; Zhen Chen; Jun Li; Jianye Peng; Jian Wang; Mingjun Feng; Tiancheng Liu; Mengli Zhang; Xian Wu; Fen Ai; Caijie Shen (Genes & Genomics, 2024)

Evapotranspiration partitioning based on underlying conductance in a complex tree-grass orchard ecosystem in the humid area of southern China - Ningbo Cui; Shunsheng Zheng; Shouzheng Jiang; Mingjun Wang; Lu Zhao; Ziling He; Yu Feng; Yaosheng Wang; Daozhi Gong; Chunwei Liu; Rangjian Qiu (Agricultural and Forest Meteorology, 2024)

Interactions between climate warming, herbicides, and eutrophication in the aquatic food web - Tao Wang; Peiyu Zhang; Jorge García Molinos; Jiayi Xie; Huan Zhang; Huan Wang; Xiaoqi Xu; Kang Wang; Mingjun Feng; Haowu Cheng; Min Zhang; Jun Xu (Journal of Environmental Management, 2023)

Bridging resource disparities for sustainable development: A comparative analysis of resource-rich and resource-scarce countries - Yanchao Feng; Jin Hu; Sahar Afshan; Muhammad Irfan; Mingjun Hu; Shujaat Abbas (Resources Policy, 2023)

Octyl gallate targeting the 3C-like protease exhibits highly efficient antiviral activity against swine enteric coronavirus PEDV - Mingjun Su; Baishuang Yin; Xiaoxu Xing; Zijian Li; Jiyu Zhang; Shufeng Feng; Lu Li; Feiyu Zhao; Xu Yang; Shiping Yu; Jun Wang; Yongchen Zhang; et al. (Veterinary Microbiology, 2023)

Weight–Length Relationship Analysis Revealing the Impacts of Multiple Factors on Body Shape of Fish in China - Yushan Li; Mingjun Feng; Liangliang Huang; Peiyu Zhang; Hongxia Wang; Jingwei Zhang; Yuehan Tian; Jun Xu (Fishes, 2023)
The weight–length relationship (WLR) of fish is a crucial tool in fish biology research and has received extensive attention. However, fish growth is influenced by many factors, and the WLR also changes accordingly. Our aim was to investigate how fish body shape is affected by various factors by analyzing the existing parameters of the relationship between fish body length and weight. We analyzed 198,354 fish specimens belonging to 402 species of 82 families in China and investigated the change of fish body shape in the function of their ecology. Herbivorous fish tended to be shorter and fatter than carnivorous fish, and omnivorous fish fall somewhere in between. This difference could be due to variations in feeding habits and the availability of food sources. Additionally, fish living in lentic waters tended to have a shorter and fatter body shape compared to those living in lotic waters. This could be attributed to differences in swimming behavior in these environments. Furthermore, our results showed that the b value decreased as altitude increased, and fish tended to be thinner and longer due to lower oxygen and temperature levels in high-altitude waters. Overall, our study provides valuable insights into the WLR of fish and the impact of multiple factors on fish body shape.

Zonotopic resilient state estimation for unmanned surface vehicles subject to integrity attacks - Jitao Li; Yujia Wang; Xing Liu; Feng Yao; Mingjun Zhang (Ocean Engineering, 2023)

Stoichiometric stability of aquatic organisms increases with trophic level under warming and eutrophication - Mingjun Feng; Haowu Cheng; Peiyu Zhang; Kang Wang; Tao Wang; Huan Zhang; Huan Wang; Libin Zhou; Jun Xu; Min Zhang (Science of The Total Environment, 2023)

Energy-saving production of high value-added foamed glass ceramic from blast furnace slag and hazardous wastes containing heavy metal ions - Mingjun Li; Feng Zheng; Jiao Wang; Donghua Jia; Xiaodong Mao; Peng Li; Qiang Yuan; Qiang Zhen; Yi Yu (Journal of Cleaner Production, 2023)

The Mitochondrial-Derived Peptide MOTS-c Attenuates Oxidative Stress Injury and the Inflammatory Response of H9c2 Cells Through the Nrf2/ARE and NF-κB Pathways - Caijie Shen; Jian Wang; Mingjun Feng; Jianye Peng; Xiangfeng Du; Huimin Chu; Xiaomin Chen (Cardiovascular Engineering and Technology, 2022)

The Antioxidant Role of Selenium via GPx1 and GPx4 in LPS-Induced Oxidative Stress in Bovine Endometrial Cells - Samson O. Adeniran; Peng Zheng; Rui Feng; Elikanah O. Adegoke; Fushuo Huang; Mingjun Ma; Ziming Wang; Olamigoke O. Ifarajimi; Xiaoyu Li; Guixue Zhang (Biological Trace Element Research, 2022)

Aberrant Methylation Changes Detected in Cutaneous Squamous Cell Carcinoma of Immunocompetent Individuals - Liming Li; Mingjun Jiang; Qinghua Feng; Nancy B. Kiviat; Joshua E. Stern; Stephen Hawes; Steve Cherne; Hiep Lu (Cell Biochemistry and Biophysics, 2015)

PM10 concentration in urban atmosphere around the eastern Tien Shan, Central Asia during 2007–2013 - Shengjie Wang; Mingjun Zhang; María Cruz Minguillón; Xiaoyu Zhang; Fang Feng; Xue Qiu (Environmental Science and Pollution Research, 2015)

Comparison of surface air temperature derived from NCEP/DOE R2, ERA-Interim, and observations in the arid northwestern China: a consideration of altitude errors - Shengjie Wang; Mingjun Zhang; Meiping Sun; Baolong Wang; Xiaoyan Huang; Qiong Wang; Fang Feng (Theoretical and Applied Climatology, 2015)